Pengaruh Penggunaan Media Sosial dalam Pemasaran Rumah Sakit: Systematic Review: Studi Kasus RS. Proklamasi Rengasdengklok - Amilia Gunawan; Aria Kartika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Hospitals as organizations that serve the interests of many people also need to carry out marketing to improve the quality of service and also the company's image in the community, so that hospital public relations need to work optimally using available media, one of which is social media to market their service products. This study aims to determine the effect of the use of social media in hospital marketing at RS. Proklamasi Rengasdengklok. In this case, the researcher used the systematic review method, namely an evidence-based method to conduct a systematic review. The source of the article was taken from related articles published in 2019-2022 using Google Scholar and PubMed. The inclusion criteria were (1) research conducted on the use of social media in marketing in hospitals during the last 3 years, (2) all descriptive and analytical studies with different methodologies, and (3) only studies in English, using the keyword